Wildfire erosion as a pathway for endocrine disrupting chemical contamination in watersheds: a scoping review - Fitzhugh, Hannah S.; Mateus, Marcos D. (Frontiers in Water, 2026)
Synthetic endocrine disrupting chemicals (EDCs) are pervasive micropollutants found in aquatic, terrestrial, and anthropogenic systems that cause irreversible damage to human and wildlife hormonal function. Although research is underway to monitor EDCs in water, the effect of wildfire erosion on EDC contamination in watersheds is underexplored. Wildfires modify soil and vegetation properties, often leading to increased erosion and sediment, especially following rainfall. Some synthetic EDCs that are known to persist in watersheds are heat-resistant and mobile, such as polybrominated diphenyl ethers (PBDEs), per- and perfluoroalkyl substances (PFAS), and polychlorinated biphenyls (PCBs). Wildfires have the potential to transport and concentrate EDCs from terrestrial environments into aquatic systems via post-fire runoff. A scoping review was conducted in Elsevier Scopus to assess knowledge on wildfire-related mobilization of synthetic EDCs. Six target chemical groups were searched using broad wildfire-associated terms. From 164 screened records, 11 met inclusion criteria. The available studies spanned several EDC groups and focused largely on air (n = 8) and soil (n = 4) matrices, with some work involving biota. No research examined EDC transport in aquatic environments. Based on the evidence identified through this scoping review, we propose that wildfire-driven erosion may increase EDC transport into watersheds, posing a cumulative and significant threat to water quality. In response to these findings, we present a targeted post-wildfire EDC monitoring panel to support early detection and timely management actions. We also outline key research priorities to advance understanding of EDC behavior in post-fire landscapes. We aim to alert water quality monitoring professionals to this underrecognized hazard and to highlight the urgent need for focused research on its implications for both public and environmental health.